2016
DOI: 10.18632/oncotarget.7451
|View full text |Cite
|
Sign up to set email alerts
|

Ioncopy: a novel method for calling copy number alterations in amplicon sequencing data including significance assessment

Abstract: Recently, it has been demonstrated that calling of copy number alterations (CNAs) from amplicon sequencing (AS) data is feasible. Most approaches, however, require non-tumor (germline) DNA for data normalization. Here, we present the method Ioncopy for CNA detection which requires no normal controls and includes a significance assessment for each detected alteration.Ioncopy was evaluated in a cohort of 184 clinically annotated breast carcinomas. A total number of 252 amplifications were detected, of which 183 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 21 publications
(23 reference statements)
0
31
0
Order By: Relevance
“…Both reported a high concordance rate (>95 and 97%, respectively) between copy number data obtained by FISH and targeted NGS data. Applying the bioinformatics tool Ioncopy, Budczies et al (2016) reported similar results with fresh tissue and a specific gene panel for targeted NGS that is different from the one employed here. Our results demonstrate that our NGS-based method could be used in an up-front diagnostic setting with a specificity of 100%.…”
Section: Discussionmentioning
confidence: 59%
“…Both reported a high concordance rate (>95 and 97%, respectively) between copy number data obtained by FISH and targeted NGS data. Applying the bioinformatics tool Ioncopy, Budczies et al (2016) reported similar results with fresh tissue and a specific gene panel for targeted NGS that is different from the one employed here. Our results demonstrate that our NGS-based method could be used in an up-front diagnostic setting with a specificity of 100%.…”
Section: Discussionmentioning
confidence: 59%
“…Currently, oncologists are testing novel, molecularly targeted agents for treating HCC. Therefore, in an era of precision cancer medicine, monitoring clinically relevant genetic alterations is important for stratifying patients for targeted therapies[9]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms that govern expression levels of the PD‐ligands, such as PD‐L1, are currently not well understood. A straight‐forward mechanism that received surprisingly little attention until now are copy number changes (Albertson, ; Conrad et al, ; Zack et al, ; Zarrei et al, ) of the coding regions, which could in principle be easily detected by FISH or massive parallel sequencing approaches employed for routine diagnostics (Budczies et al, ; Endris et al, ; Stenzinger et al, ). Since the work by Green et al () on Hodgkin lymphoma, amplification of PD‐L1 in tumors has so far only been described for basal‐like and triple negative breast cancer (Ali et al, ; Barrett et al, ; Sabatier et al, ), gastric cancer (Bass et al, ), and a subgroup of lung cancer (Goldmann et al, ; Ikeda et al, ).…”
Section: Introductionmentioning
confidence: 99%